Orphans of the Motherland: Puerto Rican Images of Spain in Jacobo Morales's Linda Sara - Wadda C. Ríos-Font (Studies in 20th & 21st Century Literature, 2006)
Puerto Rican identity has been confounded by Puerto Rico's prolonged colonial relationship to Spain (nearly 80 years longer than that of most other Latin American colonies) and its abrupt change in status to that of United States protectorate in 1898 after the Spanish American War. Increasingly, Puerto Rican identity has been theorized in sole reference to the political relationship with the United States. The residual presence of Spain and Spaniards in the construction of the new Puerto Rican collective, and the denial or nostalgia that might still be elicited by the former empire, have gradually receded into the background. Perhaps surprisingly, the presence of Spain and reactions to it find their widest outlet in popular culture. This article analyzes the complex portrayal of the continuing substratum of the Spanish heritage in Puerto Rico in one example from Puerto Rican popular culture—Jacobo Morales's 1994 film Linda Sara. The film's characters either willingly or unknowingly falsify their Spanish past, recounting their (hi)story according to their present needs.
Keywords: Puerto Rico; Spain; Linda Sara; Jacobo Morales; colonialism; United States; protectorate; identity